LEGALITY OF E-COURT IN THE LEGAL REFORM TOWARDS A JUDICIAL SYSTEM WITH LEGAL CERTAINTY - Mulkan, Hasanal; Addink, Henk; Saraya, Sitta; Santoso, Andrianto Budi (Jurnal Pembaharuan Hukum, 2024)
The development of existing technology has an impact on the public service system in terms of online criminal case registration, online payments, online summons, and online trials. This study aims to determine the implementation of the Electronic-Based Government System application in services at the District Court. The research method used in this study was normative legal research. The results of the study show that the existence of e-court has had a major impact on the progress of the justice system in Indonesia while realizing justice based on simplicity, speed and low cost. The impact of the e-court system itself on the judicial process with the increasing development of digital technology, the transformation of courts into modern courts that utilize digital information technology to the maximum is a necessity. The results of the study are expected to provide strategic recommendations for the District Court in optimizing the implementation of SPBE in order to achieve the goals of good governance and improve the quality of public services.